2019
DOI: 10.1186/s41983-019-0078-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences among epileptic patients: a comparison of epilepsy and its impacts on demographic features, clinical characteristics, and management patterns in a tertiary care hospital in Egypt

Abstract: Background: Epilepsy is one of the most common neurological conditions. We aimed to identify sex differences in the demographic, clinical features, and treatment strategies in epileptic patients. Objectives: To analyze and compare the differences in the impact of epilepsy on the socio-demographic characteristics of male and female patients along with gender differences in various types of epilepsies and treatment strategies. Material and methods: A record-based study for 1000 individuals attending the epilepsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…Usually the first seizures between 12 and 18 years of age are well recognized (11,12). There are many studies showing female dominance for JME (13,14,15). In our study, in accordance with the literature, 48 (64%) of the patients were female, 27 patients (36%) were male and the female-male ratio was 1.7/1.…”
Section: Discussionsupporting
confidence: 91%
“…Usually the first seizures between 12 and 18 years of age are well recognized (11,12). There are many studies showing female dominance for JME (13,14,15). In our study, in accordance with the literature, 48 (64%) of the patients were female, 27 patients (36%) were male and the female-male ratio was 1.7/1.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical Studies. Some studies have reported a greater rate of generalized tonic-clonic seizures in males (Hauser et al, 1993;Kishk et al, 2019), although other studies have found either no sex difference (Carlson et al, 2014) or increased generalized tonicclonic seizures in females (Mullins et al, 2007). The variability in these effects across studies may reflect relatively small sample sizes and/or differences in reporting across countries.…”
Section: A Generalized Motor Seizuresmentioning
confidence: 98%
“…31 Variable results were reported about sex difference for seizure types, some showed that idiopathic generalized epilepsy or multiple seizure types are more common in females. 32 Other reported that atonic seizures were more common in males with generalized epilepsy, and that autonomic, visual, and psychic symptoms associated with nonacquired focal epilepsy, were more common in females. 33 The current study reported no one in the control group with positive anti-NMDAR antibodies, in contrast to other studies which showed positivity in the serum of healthy persons as in USA in 2014 (0.4%) and in Germany in 2013 (3%).…”
Section: Resultsmentioning
confidence: 98%